TRANSFORMATIVE ARCHITECTURE OF PROPHETIC SOCIAL SCIENCES BY HUSNI MUADZ: SYNTHESIS OF LINGUISTICS, SYSTEMS, AND QUR'ANIC PRACIS - Lalu Ahmad Rizkan; Agus Dedi Putrawan (Tahiro : Journal of Peace and Religious Mederation, 2025)
This article analyzes the intellectual architecture of Husni Muadz, who developed Transformative Prophetic Social Science through a synthesis of Western scientific methodology and Islamic epistemology. By combining Linguistics, General System Theory (GST), and Pragmatics with Qur'anic values, Sufism ethics, and Islamic philosophy, Muadz built a paradigm that is not only diagnostic but also operational. This study maps two main phases of Muadz's development: the theoretical formulation phase (1991–2010), which produced Transformative Social Sciences and the Praxis-Recognitive Learning Model; and the practical transformation phase (2010–2021), which gave birth to social technologies such as the Meeting School and Pragmatics of the Qur'an. The research findings show that Muadz's container–content approach enables the integration of systemic analysis and a transcendent ethical orientation, thus diagnosing structural inequalities while offering a concrete, low-cost, and easily replicable mechanism for social transformation. Furthermore, the praxis-recognitive model and the use of Qur'anic speech act theory establish a system of moral accountability that connects ethical intentions with social action. This study confirms Muadz's significant contribution in expanding the framework of Prophetic Social Science by presenting an applicable methodology relevant to character development, social liberation, and community development.